Effects of L-carnitine and cryodevices on the vitrification and developmental competence of invitro fertilized buffalo oocytes - Elmetwally, Mohammed A; Mostagir, Amira M; Bazer, Fuller W; Montaser, Abdelmonem; Badr, Magdy; Eldomany, Wael; Eldesoky, Ashraf; Elghareeb, Mona M; Jaimes, Daniela; Lenis, Yaser Y; Zaabel, Samy M (Journal of the Hellenic Veterinary Medical Society, 2022)
In the current, study the effect of the addition of L-carnitine (LC) in in vitro maturation (IVM) medium for buffalo oocytes and different cryo-devices on developmental competence. They were matured in IVM medium supplemented with 0.0, 0.3, 0.6 and 1.2 mg/mL of LC and vitrified by using either straw (ST), open pulled-straw (OPS), solid surface vitrification (SSV). The effects of LC during invitro fertilization and invitro culture on the developmental potential were examined. ST showed a higher recovery rate when using 0.6 mg/ml; viability rate (VR) when using 0.3mg/ml and lower zona pellucida (ZP) and cytoplasmic abnormalities when using 1.2 mg/ml LC (P<0.05). OPS showed a higher recovery and viability rates when using 0.3 mg (P<0.05). SSD showed a higher recovery and VR when using 0.6 mg/ml LC (P<0.05). Maturation and fertilization rates were increased when using 0.3 mg LC and OPS (P<0.05). Cleavage was increased in 0.3 (OPS) and 0.6 mg LC (SSD). The blastocyst rate was increased in 0.3 (OPS) and 0.6 mg/ml (SSD) (P< 0.05). In conclusion, 0.3 mg/ml LC and OPS gives a higher recovery and viability rates but 0.6 mg/ml LC and of both SSD and ST gives a higher recovery and viability rates.